Perancangan Website E-Commerce IFSTORE Dengan Metode Waterfall - Diyah Saputri, Rasikha; Resad Setyadi (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2023)
Technology is reportedly developing very rapidly. Internet technology is often heard today, namely the advances in information technology. Technological progress is heading in a more user-friendly direction, which means it makes it easier for users to understand and use Internet functions. In the past, e-commerce activities were carried out through direct products, but the rapid development of the Internet has replaced this model. The objective of this online shopping platform is to bringing shopping convenience to customers without the need to visit offline stores. The research approach used is qualitative, with the application of the SDLC Waterfall model or linear sequence. in the process of analyzing the needs intensively in web development and determining the needs of applications that will be used to be practically understood by e-commerce web users. Designing an e-commerce website using PHP becomes a scripting language and XAMPP becomes a database for data storage. the way of testing using the black box method, as well as the input data used in this paper adopts the technique of partition equivalence, that is, any dish or function that requires user input is tested based on valid or invalid values. From this research, It can be inferred that website design plays a crucial role in addressing business challenges competition, especially in the clothing and accessories sales sector, changing product data and deleting product data making news. that is fast, precise, and attractive to customers.